Emission spectrum modeling of white LEDs light source with using Gaussian function - Nguyen, Quang-Khoi (Photonics Letters of Poland, 2023)
A mathematical model for emission spectrum modeling which is simple, easy to use, easy to understand and apply; is built and proposed. Then, the model can applied to design emission spectrum with using LED, study the optical and color performance of emitted white light spectrum. This effiecient method is helpful for researcher working in solid state lighting (SSL) field, spectrum design for light source, optimize the optical and electrical performace for any specify desired light source. Full Text: PDF References E.F. Schubert, J.K. Kim, "Solid-State Light Sources Getting Smart", Science, 308, 1274 (2005) CrossRef N. Narendran, Y.J. Gu, "Life of LED-based white light sources", Display Technol. 2005, 1, 167-171. CrossRef E. Schubert, Light-Emitting Diodes (Cambridge: Cambridge University Press 2006). CrossRef Y. Ohno. "Spectral design considerations for white LED color rendering", Opt. Eng. 4411, 111302 (2005). CrossRef J. Huaizhou, S. Jin, K. Yuan, S. Cen. "Modification to a single Gauss simulation of a phosphor coated light-emitting diode", Opt. Eng. 52, 087102 (2013). CrossRef H. Jin, S. Jin, K. Yuan, and S. Cen. "Two-Part Gauss Simulation of Phosphor-Coated LED", IEEE Photonics J. 5, (2013). CrossRef G-Q Xu, J-H Zhang, G-Y Cao, M-S Xing, D-S Li, J-J Yu,. "Solar spectrum matching using monochromatic LEDs", Lighting Res. Technol. 49, 4 (2016) CrossRef T-H. Yang, H-Y. Huang, C-C. Sun, B. Glorieux, X-H. Lee, Y-W. Yu, T-Y. Chung "Noncontact and instant detection of phosphor temperature in phosphor-converted white LEDs", Sci. Rep. 8, 296 (2018). CrossRef Q. Chen, X. Jin, L. Xue. "Modeling and optimization of multi-LED solar spectrum synthesis with widely-tuning radiant flux output", Optik 180, 276-284 (2019) CrossRef L. Liu. "LED Solar Spectrum Computer Simulation Based on Non-dominated Sorting Genetic Algorithm", J. Phys. Conf. Ser., 1578, 012103 (2020). CrossRef L. Bachouch , N. Sewraj , P. Dupuis , L. Canale, G. Zissis, L. Bouslimi, and L. El Amraoui. "An Approach for Designing Mixed Light-Emitting Diodes to Match Greenhouse Plant Absorption Spectra", Sustainability 13, 4329 (2021) CrossRef Z. Liu, F. Li, G. Huang, J. Wei, G. Jiang, Y. Huang, X. Jin and Q. Li. "Spectral Design of Light-Emitting Diodes for Plant Photosynthesis Based on Quantum Dots", IEEE Access, 9, 156229-156238 (2021). CrossRef S. Bauer. "Blue-Light Hazard of Light-Emitting Diodes Assessed with Gaussian Functions", Int. J. Environ. Res. Public Health, 18, 680 (2021). CrossRef S. Benkner, A. Herzog, S. Klir, W.D. Van Driel and T.Q. Khanh. "Advancements in Spectral Power Distribution Modeling of Light-Emitting Diodes", IEEE Access, 10, 83612-83619 (2022). CrossRef